Monograph No. 26: Reducing Stigma and Discrimination for People Experiencing Problematic Alcohol and Other Drug Use - Lancaster, K; Seear, K; Ritter, A (UNSW Sydney, 2018)
This project aimed to understand experiences of stigma and discrimination for people experiencing problematic alcohol and other drug (AOD) use in Queensland. Specifically, the research examined: • Experiences of stigma and discrimination; • The potential for legislation to be stigmatising; • The settings and sectors in which stigma and discrimination occur; • The impacts of stigma and discrimination on health and wellbeing and in particular on recovery and the ability to reconnect with the community; and • Circumstances where stigma is not experienced, and evidence of what works to address stigma and discrimination. In this report, stigma and discrimination are defined as follows: Stigma is labelling and stereotyping of difference, at both an individual and structural societal level, that leads to status loss (including exclusion, rejection and discrimination). Discrimination is the lived effects of stigma – the negative material and social outcomes that arise from experiences of stigma. Both stigma and discrimination rely on societal structures and systems that facilitate and create the conditions for their operation (for example unequal power is one such condition). In this project we sought to identify effective ways to reduce stigma and discrimination and provide recommendations derived from the research findings to support implementation actions by the Queensland government.
DPMP Monograph Series; 26